Gelatinase-sensitive nanoparticles loaded with photosensitizer and STAT3 inhibitor for cancer photothermal therapy and immunotherapy - Lin-Lin Bu (BMC, 2021)
Abstract Matrix metalloproteinase (MMP) 2 and 9 are the family members of proteases normally up-regulated in tumor to enhance the invasion and metastatic of tumor cells, and are associated with poor outcome of head and neck squamous cell carcinomas (HNSCCs). In the present work, MMPs-degradable gelatin nanoparticles (GNPs) are simultaneously loaded with photosensitizer indocyanine green (ICG) along with signal transducer activator of transcription 3 (STAT3) inhibitor NSC74859 (NSC, N) for efficient photothermal therapy (PTT) and immunotherapy of HNSCCs. In the tumor tissue, Gel-N-ICG nanoparticle was degraded and encapsulated ICG and NSC were effectively released. Under near-infrared (NIR) irradiation, the released ICG nanoparticles enabled effective photothermal destruction of tumors, and the STAT3 inhibitor NSC elicited potent antitumor immunity for enhanced cancer therapy. Based on two HNSCC mouse models, we demonstrated that Gel-N-ICG significantly delayed tumor growth without any appreciable body weight loss. Taken together, the strategy reported here may contribute that the stimuli-responsive proteases triggered nanoplatform could reduce tumor size more effectively in complex tumor microenvironment (TME) through combination of PTT and immunotherapy. Graphical Abstract